VD_FINDINFO HC / 2016 / 125 vom 29. Januar 2016 - VD Tribunal cantonal (2016)
CONTRAT DE TRAVAIL, RÉSILIATION IMMÉDIATE, MAXIME DE DISPOSITION, INDEMNITÉEN GÉNÉRAL | 337 CO, 337c CO, 58 al. 1 CPC (CH)